2017
DOI: 10.1002/jbm.b.34028
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of chelate‐setting α‐tricalcium phosphate cement using sodium citrate and sodium alginate as mixing solution and its in vivo osteoconductivity

Abstract: Moldable and injectable calcium-phosphate cements (CPCs) are material candidates for bone replacement applications. In the present study, we examined the effectiveness of sodium alginate and sodium citrate additives to the liquid phase of CPC, in improving its handling property as well as mechanical strength. The use of these additives enhanced the handling property significantly, in terms of consistency as compared to CPC without additives due to the liquefying effect caused by the adsorption of citrate ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In contrast, SCB‐treated constructs had a significantly low calcium amount compared with PBS‐treated and untreated constructs. This result was attributed to the chelating ability of sodium citrate for calcium (Konishi et al, ) and mineralized ECMs deposited within the cell constructs were lysed by SCB. The results of FT‐IR also showed peak reductions in bone‐specific proteins (amides I and II) as well as carbonate and phosphate ions related to mineralized matrices.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SCB‐treated constructs had a significantly low calcium amount compared with PBS‐treated and untreated constructs. This result was attributed to the chelating ability of sodium citrate for calcium (Konishi et al, ) and mineralized ECMs deposited within the cell constructs were lysed by SCB. The results of FT‐IR also showed peak reductions in bone‐specific proteins (amides I and II) as well as carbonate and phosphate ions related to mineralized matrices.…”
Section: Discussionmentioning
confidence: 99%
“…The setting time and microstructure of biocements are influenced by ALGH [ 111 , 112 ]. It was found that the ALGH additive increased the compressive strength, cohesion and toughness of the biocements [ 97 , 113 , 114 , 115 ]. Furthermore, the composite biocements exhibited favorable osteoconductivity and bioresorbability [ 113 ].…”
Section: Algh-hap Biocementsmentioning
confidence: 99%
“…It was found that the ALGH additive increased the compressive strength, cohesion and toughness of the biocements [ 97 , 113 , 114 , 115 ]. Furthermore, the composite biocements exhibited favorable osteoconductivity and bioresorbability [ 113 ]. In another investigation, it was demonstrated that the addition of ALGH to biocements facilitated hardening reactions and improved the mechanical properties [ 116 ].…”
Section: Algh-hap Biocementsmentioning
confidence: 99%